Scrotal hemangiosarcoma in a Large White boar - Renato Luiz Silveira; Ana Claudia de Menezes Cruz; Phillipe Bauer de Araújo Doria; Joao Marcelo Silva Silveira; Carlos Otávio de Paula Vasconcelos; André Luis Rios Rodrigues; Eduardo Kenji Nunes Arashiro; Hassan Jerdy; Mariana Tavares Dias; Eulógio Carlos Queiroz de Carvalho; Carlos Henrique Campello Costa (Ciência Rural, 2021)
ABSTRACT: Tumors are rarely diagnosed in swine specie because of the short lifespan of production animals. Normally, these tumors do not present any clinical signs and are often detected at the time of slaughter. A 2-year-old Large White boar, used in the reproductive management of a farm and without a history of pre-existing problems, was examined for skin lesions on the scrotum. Samples were collected from skin segments containing lesions for histopathological and immunohistochemical diagnosis. Microscopically, the nodes in the scrotum pouch consisted of poorly demarcated, highly cellular, expansile, and multifocally invasive neoplasms, composed of immature endotheliocytes organized into neovascular formations. The tumor cells were pleomorphic, slightly oval to spindle-shaped, with eosinophilic cytoplasm and hyperchromatic nuclei with one to three nucleoli. All the nodules analyzed were compatible with hemangiosarcoma. After immunohistochemical evaluation, for the quantification of tissue angiogenesis the neoplastic cells immunoexpressed the CD31 monoclonal antibodies and factor VIII, through the identification of proteins expressed on the surface of endothelial cells. The Ki67 cell proliferation marker was positive in approximately 10% of the neoplastic cells, demonstrating a high degree of malignancy. Hemangiosarcoma in swine species has already been identified in several organs and tissues; however, to date, no study has demonstrated the diagnosis of this condition on the skin of the scrotum, as reported in this study. Therefore, it is expected that this report will contribute to the knowledge of the frequency of neoplasms in swine species.